1977
DOI: 10.1159/000207895
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte <i>δ</i>-Aminolaevulinic Acid Dehydratase, Urinary Porphyrins and Porphyrin Precursors in Iron Deficiency Anaemia

Abstract: In 20 iron deficient patients and 21 normal controls the activity of the enzyme δ-ALA dehydratase of erythrocytes was assayed. In addition the urine porphyrins and porphyrin precursor excretions were measured. It was found that in sideropenic patients the erythrocyte δ-ALA dehydratase activity was almost constantly higher than in normals; the difference of the mean values being statistically significant (p < 0.005). A significant diminution of δ-ALA (p < 0.0025) urine excretion was observed, whereas the urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1977
1977
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
1
2
1
Order By: Relevance
“…The results of the present and earlier studies (Lichtman & Feldman, 1963;Battistini, Morrow, Ginsburg, Thompson, Moore & Goldberg, 1971;Mazza, Pescarmona, Bianco, Ricco & Gallo, 1972) suggest that iron-deficiency anaemia has no effect on erythrocyte ALA dehydratase. This is contrary to the recent findings Chalevelakis, Lyberatos, Manopoulos, Pyrovolakis & Gardikas, 1977) that erythrocyte ALA dehyd- …”
Section: Discussioncontrasting
confidence: 98%
“…The results of the present and earlier studies (Lichtman & Feldman, 1963;Battistini, Morrow, Ginsburg, Thompson, Moore & Goldberg, 1971;Mazza, Pescarmona, Bianco, Ricco & Gallo, 1972) suggest that iron-deficiency anaemia has no effect on erythrocyte ALA dehydratase. This is contrary to the recent findings Chalevelakis, Lyberatos, Manopoulos, Pyrovolakis & Gardikas, 1977) that erythrocyte ALA dehyd- …”
Section: Discussioncontrasting
confidence: 98%
“…Studies on the effect of iron deficiency on ALA-D activity had given conflicting results. Our finding of a non-reticulocyte related increase, agrees with some previous observations [32,34,36,53] while it is in contrast with others [ 16,33,35]. The precise mechanism by which ALA-D activity, as well as its sensitivity to low lead levels, is enhanced in iron deficiency anaemia, are far from clear.…”
Section: Discussionsupporting
confidence: 90%
“…Whole blood levels of ^-ALAD are infiuenced by a variety of factors such as plasma copper, whole blood lead levels and alcohol consumption (Gibson et al, 1955;Moore et al, 1971;Campbell et al, 1977;Chalevelakis et al, 1977), but in none of our patients did these differ from normal controls. Other factors include blood aluminium levels , which were normal in the psoriasis and mycosis fungoides groups, and magnesitmi, which is under study.…”
Section: Discussionmentioning
confidence: 57%
“…Duplicate blood samples were obtained whenever possible, and all were taken at approximately the same time of day. Haemoglobin, plasma copper and aluminium, and blood lead were estimated as they are known to influence 5-ALAD levels (Gibson, Neuberger & Scott, 1955j Campbell et al, 1977Chalevelakis et al, 1977;, and no variation was found between the test and control groups.…”
Section: Summarŷmentioning
confidence: 99%